2016
DOI: 10.3389/fncel.2016.00260
|View full text |Cite
|
Sign up to set email alerts
|

BACE1 RNAi Restores the Composition of Phosphatidylethanolamine-Derivates Related to Memory Improvement in Aged 3xTg-AD Mice

Abstract: β-amyloid (Aβ) is produced by the β-secretase 1 (BACE1)-mediated enzymatic cleavage of the amyloid precursor protein through the amyloidogenic pathway, making BACE1 a therapeutic target against Alzheimer’s disease (AD). Alterations in lipid metabolism are a risk factor for AD by an unknown mechanism. The objective of this study was to determine the effect of RNA interference against BACE1 (shBACEmiR) on the phospholipid profile in hippocampal CA1 area in aged 3xTg-AD mice after 6 and 12 months of treatment com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 82 publications
2
26
0
Order By: Relevance
“…1A). These observations were supported by our previous studies, which demonstrated that BACE1 RNAi (BACE1-KD) reduces BACE1 protein levels in both primary neuronal cultures and the injected brain region of an Alzheimer´s mice model by approximately 50% (D Piedrahita, Castro-Alvarez, Villamil-Ortiz et al 2016). Glutamate (125 µM) increased hyperphosphorylated tau (AT8) levels in the shSCRmiR (control) group (p<0.0001) (Fig.…”
Section: Bace1 Silencing Provides Neuroprotection and Reduces Tau Hypsupporting
confidence: 77%
See 2 more Smart Citations
“…1A). These observations were supported by our previous studies, which demonstrated that BACE1 RNAi (BACE1-KD) reduces BACE1 protein levels in both primary neuronal cultures and the injected brain region of an Alzheimer´s mice model by approximately 50% (D Piedrahita, Castro-Alvarez, Villamil-Ortiz et al 2016). Glutamate (125 µM) increased hyperphosphorylated tau (AT8) levels in the shSCRmiR (control) group (p<0.0001) (Fig.…”
Section: Bace1 Silencing Provides Neuroprotection and Reduces Tau Hypsupporting
confidence: 77%
“…Inhibition of this enzyme has been viewed as an Aβ-lowering therapeutic intervention, but several problems have prevented BACE1 inhibitors from advancing to pivotal clinical trials, especially because BACE1 has multiple functional subunits ). However, we and others have found that BACE1 targeting improves longterm spatial memory and prevents Aβ plaques and tau aggregation Sierant et al 2009;Villamil-Ortiz et al 2016), with a reduction of 50% compared to the upregulated condition in neurodegeneration ).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Decreased expression and activity of BACE1 reduces progressive deposition of Aβ and is associated with synaptic pathology in animal and cell‐based models of AD (Villamil‐Ortiz et al . ; Peters et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…These deficits in long-term synaptic plasticity correlate with the accumulation of intraneuronal βA and NTFs formation. Interestingly, silenced BACE1 (main enzyme involved in the production of βA), in the hippocampus using adenoassociated viral vectors reduces the hyperphosphorilation of tau (Piedrahita et al, 2016) and improve cognitive function at 6 months and 12 months post-treatment, presenting a balanced phospholipid composition, by the reduction of saturated fatty acid (stearic acid (18:0), palmitic acid (16:0)) and increase of poli-unsaturated fatty acid (docosahexaenoic acid, DHA (22:6)), which prevented the activation of pro-inflammatory signaling cPLA2/AA/COX2 in old AD mice to long-term post-therapy (Villamil-Ortiz et al, 2016). Also, the silencing of CDK5 in the CA1 hippocampal area prevents the spreading of excitoxicity to other areas of the neuronal circuit (Piedrahita et al, 2010; Castro-Alvarez et al, 2014, 2015; Posada-Duque et al, 2015a) also reversing (Piedrahita et al, 2010) or preventing neurodegeneration by reduction of paired helicoidal formations (Castro-Alvarez et al, 2014) and further, decreases the β amyloidosis production (Castro-Alvarez et al, 2015).…”
Section: Preclinical Studies and Molecular Targetsmentioning
confidence: 99%